Direct observation of temperature-/magnetic-field-induced transition between martensite and premartensite and their relaxation in Ni–Mn–In–Al alloy. (2nd March 2017) - Cheng, H; Xia, Z C; Wang, R L; Wei, M; Jin, Z; Huang, S; Shang, C; Wu, H; Zhang, X X; Xiao, G L; Ouyang, Z W
Abstract: The microstructure evolution of the transition between premartensite and martensite in Ni50 Mn34 In15.5 Al0.5 alloy was investigated directly by in situ optical microscope under various temperatures and pulsed magnetic fields. The microscopic observations at different temperatures indicate that the martensitic transition from premartensite to martensite and the reverse transition can be induced through cooling and heating respectively. A time-dependent relaxation phenomenon can be detected in the cooling process, in other words, the martensite continues to grow with holding time at temperatures between the martensite start and finish temperature, and the relaxation time to the equilibrium state at temperatures near the martensitic transition finishing temperature is shorter than that at higher temperatures. Reverse martensitic transition from martensite to premartensite induced by a pulsed magnetic field and the isothermal growth of martensite after removing the pulsed high magnetic field can be observed at a temperature of 230 K, at which the reverse transition induced by the magnetic field is partly reversible. Hence, the result here directly evidences the isothermal nature of the martensitic transition and the athermal nature of the reverse transition.